Ferric carboxymaltose for iron deficiency at discharge after acute heart failure: a multicentre, double-blind, randomised, controlled trial. Issue 10266 (12th December 2020) - Ponikowski, Piotr; Kirwan, Bridget-Anne; Anker, Stefan D; McDonagh, Theresa; Dorobantu, Maria; Drozdz, Jarosław; Fabien, Vincent; Filippatos, Gerasimos; Göhring, Udo Michael; Keren, Andre; Khintibidze, Irakli; Kragten, Hans; et al.
Summary: Background: Intravenous ferric carboxymaltose has been shown to improve symptoms and quality of life in patients with chronic heart failure and iron deficiency. We aimed to evaluate the effect of ferric carboxymaltose, compared with placebo, on outcomes in patients who were stabilised after an episode of acute heart failure. Methods: AFFIRM-AHF was a multicentre, double-blind, randomised trial done at 121 sites in Europe, South America, and Singapore. Eligible patients were aged 18 years or older, were hospitalised for acute heart failure with concomitant iron deficiency (defined as ferritin <100 μg/L, or 100–299 μg/L with transferrin saturation <20%), and had a left ventricular ejection fraction of less than 50%. Before hospital discharge, participants were randomly assigned (1:1) to receive intravenous ferric carboxymaltose or placebo for up to 24 weeks, dosed according to the extent of iron deficiency. To maintain masking of patients and study personnel, treatments were administered in black syringes by personnel not involved in any study assessments. The primary outcome was a composite of total hospitalisations for heart failure and cardiovascular death up to 52 weeks after randomisation, analysed in all patients who received at least one dose of study treatment and had at least one post-randomisation data point. Secondary outcomes were the composite of total cardiovascular hospitalisations and cardiovascular death; cardiovascular death; total heart failure hospitalisations; time to first heart failure hospitalisation or cardiovascular death; and days lost due to heart failure hospitalisations or cardiovascular death, all evaluated up to 52 weeks after randomisation. Safety was assessed in all patients for whom study treatment was started. A pre-COVID-19 sensitivity analysis on the primary and secondary outcomes was prespecified. This study is registered with ClinicalTrials.gov, NCT02937454, and has now been completed. Findings: Between March 21, 2017, and July 30, 2019, 1525 patients were screened, of whom 1132 patients were randomly assigned to study groups. Study treatment was started in 1110 patients, and 1108 (558 in the carboxymaltose group and 550 in the placebo group) had at least one post-randomisation value. 293 primary events (57·2 per 100 patient-years) occurred in the ferric carboxymaltose group and 372 (72·5 per 100 patient-years) occurred in the placebo group (rate ratio [RR] 0·79, 95% CI 0·62–1·01, p=0·059). 370 total cardiovascular hospitalisations and cardiovascular deaths occurred in the ferric carboxymaltose group and 451 occurred in the placebo group (RR 0·80, 95% CI 0·64–1·00, p=0·050). There was no difference in cardiovascular death between the two groups (77 [14%] of 558 in the ferric carboxymaltose group vs 78 [14%] in the placebo group; hazard ratio [HR] 0·96, 95% CI 0·70–1·32, p=0·81). 217 total heart failure hospitalisations occurred in the ferric carboxymaltose group and 294 occurred in the placebo group (RR 0·74; 95% CI 0·58–0·94, p=0·013). The composite of first heart failure hospitalisation or cardiovascular death occurred in 181 (32%) patients in the ferric carboxymaltose group and 209 (38%) in the placebo group (HR 0·80, 95% CI 0·66–0·98, p=0·030). Fewer days were lost due to heart failure hospitalisations and cardiovascular death for patients assigned to ferric carboxymaltose compared with placebo (369 days per 100 patient-years vs 548 days per 100 patient-years; RR 0·67, 95% CI 0·47–0·97, p=0·035). Serious adverse events occurred in 250 (45%) of 559 patients in the ferric carboxymaltose group and 282 (51%) of 551 patients in the placebo group. Interpretation: In patients with iron deficiency, a left ventricular ejection fraction of less than 50%, and who were stabilised after an episode of acute heart failure, treatment with ferric carboxymaltose was safe and reduced the risk of heart failure hospitalisations, with no apparent effect on the risk of cardiovascular death. Funding: Vifor Pharma.